2020
DOI: 10.32598/ppj.24.4.60
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and histological effect of fractionated neem leaf extract in healthy Wistar rats

Abstract: Introduction: In recent years, the growing research towards new drugs has been targeted on plant-based drugs, and Neem (Azadirachta indica) is one of the plants that have been extensively researched for its diverse medicinal properties. The study aimed to determine the effects of neem on the hematological parameters (total white blood cells, neutrophil, monocyte and eosinophil counts) and histology of some organs of rats. Methods: Fifteen healthy male Wister rats divided into control (Nm0) and experimental gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Our findings are in agreement with the findings of Ogbuewu et al (2010) [11] , who also reported non-significant variation in the values of PCV following treatment with leaf meal of Azadirachta indica in female rabbits. Non-significant variation in the mean values of PCV was also recorded by Ikwuka et al (2020) [5] after treatment with fractionated neem leaf extract in wistar rats.…”
Section: Packed Cell Volume (%)supporting
confidence: 52%
See 1 more Smart Citation
“…Our findings are in agreement with the findings of Ogbuewu et al (2010) [11] , who also reported non-significant variation in the values of PCV following treatment with leaf meal of Azadirachta indica in female rabbits. Non-significant variation in the mean values of PCV was also recorded by Ikwuka et al (2020) [5] after treatment with fractionated neem leaf extract in wistar rats.…”
Section: Packed Cell Volume (%)supporting
confidence: 52%
“…The PCV and Hb values of rabbits on test diets were not significantly (p> 0.05) different from the control group. Ikwuka et al (2020) [5] studied effect of fractionated neem leaf extract on haematological parameters of healthy Wistar rats and concluded that WBC and packed cell volume was not differed between the groups. No significant change in the neutrophil (F=0.81, P=0.47), lymphocyte (F=0.96, P=0.41), monocyte (F=1.86, P=0.20) and eosinophil (F=0.45, P=0.65) numbers (%) was reported.…”
Section: Introductionmentioning
confidence: 99%
“…A great number of the world's population; particularly Nigerians, rely on traditional medicines "for their primary healthcare needs" [9]. "These medicinal plants contain substances used for therapeutic purposes or are precursors for the synthesis of useful drugs" [9,10]. "Ginger also has high antioxidant activity" [8].…”
Section: Introductionmentioning
confidence: 99%